2017
DOI: 10.4196/kjpp.2017.21.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide attenuates refilling of intracellular calcium store in mouse pancreatic acinar cells

Abstract: Intracellular calcium (Ca2+) oscillation is an initial event in digestive enzyme secretion of pancreatic acinar cells. Reactive oxygen species are known to be associated with a variety of oxidative stress-induced cellular disorders including pancreatitis. In this study, we investigated the effect of hydrogen peroxide (H2O2) on intracellular Ca2+ accumulation in mouse pancreatic acinar cells. Perfusion of H2O2 at 300 µM resulted in additional elevation of intracellular Ca2+ levels and termination of oscillatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In this study, when parotid acinar cells were exposed to 1 mM H 2 O 2 in normal Ca 2+ buffer, there was a significant intracellular Ca 2+ accumulation, and the elevated Ca 2+ was nearly returned to baseline after the cessation of H 2 O 2 perfusion. Generally, H 2 O 2 is known to accumulate cytosolic Ca 2+ without acute cell death at concentrations from 10 µM to 5 mM in various cell types [ 16 17 18 19 20 21 22 23 24 25 ]. Thus, mouse parotid acinar cells are thought to be relative resistance to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, when parotid acinar cells were exposed to 1 mM H 2 O 2 in normal Ca 2+ buffer, there was a significant intracellular Ca 2+ accumulation, and the elevated Ca 2+ was nearly returned to baseline after the cessation of H 2 O 2 perfusion. Generally, H 2 O 2 is known to accumulate cytosolic Ca 2+ without acute cell death at concentrations from 10 µM to 5 mM in various cell types [ 16 17 18 19 20 21 22 23 24 25 ]. Thus, mouse parotid acinar cells are thought to be relative resistance to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that functionally important sulfhydryl group are present within PMCA and SERCA molecules that is localized within the catalytic and controlling centers of Ca 2+ -ATPase [ 38 39 40 ]. We previously reported that H 2 O 2 accumulates intracellular Ca 2+ by attenuating SERCA activity in pancreatic acinar cells [ 25 ]. Interestingly, in this study, H 2 O 2 failed to change Ca 2+ refilling into the ER store through SERCA by the application of Ca 2+ and Mg-ATP in permeabilized parotid acinar cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an increase in the rate of ER Ca 2+ refilling by SERCA2B would lead to ER Ca 2+ overload, which, in turn, is able to stimulate InsP 3 Rs and thereby initiate the function cross-talk between STIM and Orai proteins [ 195 ]. Paradoxically, SERCA2B inhibition by excessive production of oxidants could lead to SOCE activation as intraluminal Ca 2+ efflux through ER leakage channels is no longer counteracted by SERCA2B-mediated sequestration into ER lumen and may lead to ER Ca 2+ depletion [ 33 , 196 ].…”
Section: Ros Modulate Store-operated Ca 2+ Entry In Vascular Endothelial Cellsmentioning
confidence: 99%